Use of medicinal plants as analgesic anti-inflammatory in the Salasaca Ecuador Parish (Salud, Arte y Cuidado, 2019)
Objective: The present investigation aimed to characterize the use of medicinal plants as anti-inflammatory analgesic effect in the Salasaca Parish, Tungurahua Province, Ecuador. Methodology and Procedures: It was an observational, descriptive, field, cross-sectional and prospective investigation. The sample was calculated with a confidence level of 95%, an accuracy of 3% and a proportion of 5%, it was of 214 respondents, randomly selected by cluster sampling of the 17 districts of this Parish. A questionnaire was applied consisting of 8 questions, 2 open and 6 closed. Results: The results indicate that women are responsible for health care in the home, so they have greater ancestral knowledge of these resources compared to men. The most used plants were chamomile, flaxseed, plantain and mint. The most used form of preparation is infusion, with a non-specific dosage and frequency. No adverse effects were identified when ingested and no additional or complementary rituals are performed. Conclusion. The medicinal plants are very important for the people in the community to address problems of pain and inflammation, taking advantage of active plants provide them, and this knowledge transmitted through the experience and wisdom of practitioners, making It is possible that these practices continue to be preserved as a cultural relevant to the population.